Orofacial disease: update for the dental clinical team - Scully Crispian; Porter, Stephen R. (Edinburgh Churchill Livingstone)
Focuses on the conditions which appear in general dental practice, and provides the dental team with guidance on an area where they may be the first to pick up indications of serious systemic conditions. This is a guide to what dental practitioners and their teams need to know about oral medicine.
Keywords: Medicina oral